Association of the comorbidity of gestational diabetes mellitus and hypertension disorders of pregnancy with birth outcomes - Lin, Xingxi; Zhou, Luhan; Si, Shuting; Cheng, Haoyue; Alifu, Xialidan; Qiu, Yiwen; Zhuang, Yan; Huang, Ye; Zhang, Libi; Ainiwan, Diliyaer; Liu, Hui; Yu, Yunxian (Frontiers in Endocrinology, 2024)
Backgrounds Many pregnant women suffer from more than one pregnancy complication. However, whether those women experienced a higher risk of adverse birth outcomes is unclear. This study aims to assess the association between the comorbidity of gestational diabetes mellitus (GDM) and hypertension disorders of pregnancy (HDP) and adverse birth outcomes.The data was from the Zhoushan Maternal and Child Health Hospital electronic medical recorder system (EMRS) between 2015 and 2022. Multivariate linear regression model was used to analyze the association of GDM, HDP, and comorbidity with birth weight and gestational age, respectively. Multiple logistic regression model was used to analyze the association of GDM, HDP, and comorbidity with adverse birth outcomes.Results 13645 pregnant women were included. GDM+HDP was significantly associated with a higher risk of composite adverse neonatal outcomes (OR=1.82, 95%CI: 1.02-3.04), including preterm birth, placenta previa, and/or neonatal jaundice, a higher risk of small for gestational age (SGA) (OR=2.2, 95% CI: 1.24 3.92) and large for gestational age (LGA) (OR=2.33, 95% CI: 1.64 3.31) compared with the normal group. Further analysis showed that HDP diagnosed in the 21-27 th week comorbid with GDM had the lowest gestational age at delivery (  = -1.57, P=0.0002) and birth weight (= -189.57, P=0.0138). Moreover, combined hyperglycemia (CH) comorbid with HDP had the strongest association with reduced gestational age (= -0.83, P=0.0021).Pregnant women suffering from both GDM and HDP had a higher risk of adverse neonatal outcomes; hence, the prevent and treatment of GDM and HDP, especially their comorbidity, are very important for pregnant women.